Adaptation and validation of the work-family conflict and family-work conflict scales in portuguese nurses: 10-item version - Simães, Clara (2020)
This study presents the adaptation and validation of a Portuguese version of the Work- Family Conflict and Family-Work Conflict scales for nurses. Participants were 310 female hospital-based nurses, from the northern region of Portugal. The assessment protocol included the Portuguese 10-item Work-Family Conflict and Family-Work Conflict scales to measure the mutual interference of the work and home domains. The Portuguese version resulted from a multi-step adaptation strategy, involving direct-translation, backtranslation and a pre-test. Construct validity was assessed by exploratory principal components factor analysis and confirmatory analysis. The internal consistency reliability was calculated using Cronbach Alpha coefficients. The Cronbach Alpha coefficients for the Work-Family Conflict and Family-Work Conflict (0.91 and 0.85 respectively) indicate good reliability. The factor analysis produced two factors, explaining 69.3% of the variance, replicating the model proposed by the original authors. The confirmatory factor analysis showed a good model fit (NFI, TLI and CFI values >0.950). The RMSEA (<0.05) provided a good measure of the closeness of fit between the model and the data. The Portuguese version of the Work-Family Conflict and Family-Work Conflict scales shows good validity and reliability.